Investigating the Hypothesis of the Strength of Religious and Atheistic Belief for Alcohol and Tobacco Consumption in Heterosexual and LGBTQIA+ People - Chagas, Camila (The international journal for the psychology of religion, 2025)
The present study analyzed the effect of the strength of belief and intrapersonal religious pluralism on the at-risk consumption of alcohol and tobacco, comparing heterosexual and LGBTQIA+ people. The sample consisted of 5,007 adults, of which 1,363 (27.2%) were LGBTQIA+. Multiple linear regression models showed that there were significant differences in alcohol and tobacco consumption among people with high religiosity, medium religiosity, low religiosity and medium/low atheism, when compared to high atheism. However, the difference between the models with the control variables and the models with the strength of belief was very small, suggesting a negligible effect. This study discusses how our findings contrast with decades of research on religiosity and drug use, and with current research on belief strength and health, as well as discussing the difference between statistical significance and practical significance for advancing the field.